COMPREHENSIVE APPLIED RESEARCH ON INFLECTIONAL AND DERIVATIONAL MORPHEMES IN ENGLISH LANGUAGE ACQUISITION - Savira - Zaniar; Djuwari; Mujad Didien Afandi; Novi Rahmania Aquariza; Nailul Authar (Universitas Muhammadiyah Makassar, 2026)
Language acquisition, in particular for English as a second language (ESL), involves the knowledge of essential linguistic components such as morphemes. This research, entitled